Bartonella henselae: Clinical Manifestations and Diagnostic Workup Challenges in Patient with Fever of Unknown Origin - Misra, Neeladri (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Bartonella henselae is a zoonotic Gram-negative Bacillus associated with self-limited regional lymphadenopathy caused by close animal contact. In recent decades, a vast spectrum of clinical manifestations has been described, from mild self-limiting lymphadenopathy to disseminated disease involving multiple organs. About 30 species have been identified, and 12 have been linked to human infection, among which three are most commonly encountered clinically- Bartonella bacilliformis, which causes Oroya fever endemic to regions in Peru; Bartonella quintana that causes Trench Fever, and Bartonella henselae that causes Cat scratch disease (CSD). Trench fever was seen in World War I amongst soldiers living in trenches or closed spaces, who developed symptoms of recurrent febrile illness associated with headache, body aches, and rash that were transmitted by lice. More recently, trench fever outbreaks have been seen in densely populated spaces such as in the homeless population and refugee camps. Transmission of B. henselae is associated with cats and cat fleas. Weeks after a scratch or bite, a pustule will form at the inoculation site with associated localized lymphadenopathy. Commonly, this is a self-limiting disease. However, in immunocompromised patients and patients with predisposing factors, patients' lymphadenopathy will progress and become bacteremic, leading to endocarditis as well as aseptic meningitis. Bartonella spp. is the second most common cause of culture-negative endocarditis after Coxiella burnetii. Definitive diagnosis of Bartonella infection is often challenging due to its insidious nature and variable presentation based on the body's immune status. A clinical diagnostic challenge was encountered when a 25-year-old male presented to our hospital with a Fever of unknown origin (FUO). Initially, there was no clear etiology of the fever until a timely diagnosis of Bartonella infection was made. This case report highlights the importance of considering Bartonella as a potential etiology in patients with prolonged Fever of unknown origin (FUO), especially in endemic regions.